Present bias in the labor market: When it pays to be naive - Matthias Fahn; Regina Seibel (Johannes Kepler University of Linz, Department of Economics, 2022)
We study optimal employment contracts for present-biased employees if firms cannot commit to long-term contracts. Assuming that an employee's effort increases his chances to obtain a future benefit, we show that individuals who are naive about their present bias will actually be better off than sophisticated or time-consistent individuals. Moreover, firms might benefit from being ignorant about the extent of an employee's naivet'e. Our results also indicate that naive employees might be harmed by policies such as employment protection or a minimum wage, whereas sophisticated employees are better of
Keywords: D21; D90; J31; J32; 330; Present bias; labor markets; on-the-job search; moral hazard